2014
DOI: 10.1149/2.109406jes
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Experimental Conditions on the Catalyst Degradation in the Durability Test

Abstract: Accelerated durability tests (ADTs) were carried out for a carbon-supported platinum catalyst using a rotating disk electrode at various rotation rates for various catalyst loadings. The electrochemical surface area (ECSA) of platinum, TEM-observed relative particle size distribution, and Pt ion concentration in the electrolyte were analyzed. Their results were combined to provide the absolute change in the particle size distribution. The loss of the normalized ECSA increased with increasing the rotation rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…[30][31][32] Platinum dissolution has been extensively studied before -either in the form of a polycrystalline disk [33][34][35][36] or as a nanoparticulate catalyst. [3][4][5][6]29,[37][38][39][40] It has been shown that the electrochemical dissolution of Pt is predominantly a transient phenomenon occurring due to the interplay of Pt oxidation and reduction processes. These processes can be manipulated by changing the electrochemical treatment (scan rate, anodic and cathodic potential window), gas atmosphere, electrolyte, impurities, thickness of the catalyst layer, 3,33,36,37,[41][42][43][44] and Pt nanoparticle size as well as by the addition of alloying metals.…”
Section: -21mentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32] Platinum dissolution has been extensively studied before -either in the form of a polycrystalline disk [33][34][35][36] or as a nanoparticulate catalyst. [3][4][5][6]29,[37][38][39][40] It has been shown that the electrochemical dissolution of Pt is predominantly a transient phenomenon occurring due to the interplay of Pt oxidation and reduction processes. These processes can be manipulated by changing the electrochemical treatment (scan rate, anodic and cathodic potential window), gas atmosphere, electrolyte, impurities, thickness of the catalyst layer, 3,33,36,37,[41][42][43][44] and Pt nanoparticle size as well as by the addition of alloying metals.…”
Section: -21mentioning
confidence: 99%
“…3,48,49 Specifically, under a slow potentiodynamic regime and using the same type of carbon support, dissolution was observed to be faster the smaller the Pt nanoparticles were (see ESI, † S2.1). The effect of catalyst layer thickness on Pt dissolution, however, has only recently been proven in a conventional rotating disc electrode (RDE) study 40 by using a highly sensitive coupled analytical technique, namely SFC-ICP-MS. 39 Quite surprisingly, using these highly sensitive methods and systematically varying the catalyst loading of the electrodes showed that the Pt dissolution rate decreased as the loading increased. This was attributed to (i) an increased probability of Pt ions being trapped inside rather than diffusing out of the porous catalyst layer when the loading was higher.…”
Section: -21mentioning
confidence: 99%
“…10-12 However, the chemical and electrochemical stabilities of the carbon supports, 13,14 as well as the dissolution of platinum particles, [15][16][17] raise concern about the durability of the catalyst. Furthermore, the oxygen reduction reaction (ORR) activity per surface area of platinum (the specific activity) decreases with reducing the particle size.…”
Section: 2mentioning
confidence: 99%
“…Great efforts have been made in improving performance of those particulate catalysts by reducing particle size, 3 alloying, [4][5][6][7][8][9] or applying core-shell structure. [10][11][12] However, the chemical and electrochemical stabilities of the carbon supports, 13,14 as well as the dissolution of platinum particles, [15][16][17] raise concern about the durability of the catalyst. Furthermore, the oxygen reduction reaction (ORR) activity per surface area of platinum (the specific activity) decreases with reducing the particle size.…”
mentioning
confidence: 99%
See 1 more Smart Citation